2006
DOI: 10.3102/00346543076002249
|View full text |Cite
|
Sign up to set email alerts
|

Math Disabilities: A Selective Meta-Analysis of the Literature

Abstract: This article synthesizes published literature comparing the cognitive functioning of children who have math disabilities (MD) with that of (a) average-achieving children; (b) children who have reading disabilities (RD); and (c) children who have co-morbid disabilities (MD+RD). Average achievers outperformed children with MD on measures of verbal problem solving, naming speed, verbal working memory (WM), visual-spatial WM, and long-term memory (LTM). Children with MD outperformed co-morbid children on measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
268
4
23

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(315 citation statements)
references
References 60 publications
20
268
4
23
Order By: Relevance
“…those children whose performance was below the 25 th percentile on this standardized screening measure. The 25 th percentile cut-off has been commonly used to select children with mathematical difficulties (Swanson & Jerman, 2006). This group of children with mathematical difficulties was divided into the LAgroup (math achievement scores between the 16 th and 25 th percentile; n = 21), and the MLDgroup (math achievement scores below the 16 th percentile; n = 20).…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…those children whose performance was below the 25 th percentile on this standardized screening measure. The 25 th percentile cut-off has been commonly used to select children with mathematical difficulties (Swanson & Jerman, 2006). This group of children with mathematical difficulties was divided into the LAgroup (math achievement scores between the 16 th and 25 th percentile; n = 21), and the MLDgroup (math achievement scores below the 16 th percentile; n = 20).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Much of the existing research has identified children as having mathematical difficulties if their performance on a standardized mathematics achievement test is below the 25 th percentile (Swanson & Jerman, 2006). This cut-off score for mathematical difficulties is rather lenient and might result in a sample of children with potentially severe and potentially mild forms of mathematical difficulties, which both may show different cognitive profiles (Geary et al, 2007(Geary et al, , 2008Murphy, Mazzocco, Hanich, & Early, 2007).…”
Section: The Present Studymentioning
confidence: 99%
“…Short-term memory was initially seen as a limited capacity memory store that was subject to rapid loss due to decay (Atkinson & Shiffrin, 1968). A number of studies have shown that measures of short-term memory, such as digit span, correlate modestly with measures of higher level cognitive function, such as IQ (Mukunda & Hall, 1992;Unsworth & Engle, 2007b), reading (Swanson, Zheng, & Jerman, 2009), and arithmetic skills (Swanson & Jerman, 2006). In contrast to shortterm memory tasks such as digit span, working memory tasks involve trying to maintain information in active memory while simultaneously performing distracting or interfering activities (Case, Kurland, & Goldberg, 1982;Daneman & Carpenter, 1980).…”
Section: The Nature Of Working Memorymentioning
confidence: 99%
“…Estudos apontam uma relação consistente com conhecimento/compreensão (Floyd, Evans, & McGrew, 2003;Gelman & Butterworth, 2005;Swanson & Jerman, 2006), velocidade de processamento (Floyd et al, 2003;McGrew & Wedling, 2010), memória de curto prazo e memória operacional (Fuchs et al, 2008;Geary, 2007;) bem como inteligência fluida (Flanagan et al, 2006;Geray, 2007;Hale et al, 2007) e processamento visual (Geary, 2007;Hale et al, 2008).…”
unclassified